Neural mechanism for hypothalamic-mediated autonomic responses to light during migraine - Noseda, Rodrigo; Lee, Alice J.; Nir, Rony-Reuven; Bernstein, Carolyn A.; Kainz, Vanessa M.; Bertisch, Suzanne M.; Buettner, Catherine; Borsook, David; Burstein, Rami (Proceedings of the National Academy of Sciences - PNAS, 2017)
Migraineurs avoid light because it intensifies their headache. However, this is not the only reason for their aversion to light. Studying migraineurs and control subjects, we found that lights triggered more changes in autonomic functions and negative emotions during, rather than in the absence of, migraine or in control subjects, and that the association between light and positive emotions was stronger in control subjects than migraineurs. Seeking to define a neuroanatomical substrate for these findings, we showed that, in rats, axons of retinal ganglion cells converge on hypothalamic neurons that project directly to nuclei in the brainstem and spinal cord that regulate parasympathetic and sympathetic functions and contain dopamine, histamine, orexin, melanin-concentrating hormone, oxytocin, and vasopressin. Although the rat studies define frameworks for conceptualizing how light triggers the symptoms described by patients, the human studies suggest that the aversive nature of light is more complex than its association with headache intensification.